Occurrence of virulence factors in Cronobacter sakazakii and Cronobacter malonaticus originated from clinical samples - Holý, Ondřej; Cruz-Córdova, Ariadnna; Xicohtencatl-Cortes, Juan; Hochel, Igor; Parra-Flores, Julio; Petrželová, Jana; Fačevicová, Kamila; Forsythe, Stephen; Alsonosi, Abdlrhman (Microbial pathogenesis, 2019)
BACKGROUND: Cronobacter spp. are Gram-negative, facultative-anaerobic, non-spore forming, enteric coliform bacteria, which belongs to the Enterobacteriaceae family. Cronobacter spp. are opportunistic pathogens that have brought rare but life-threatening infections such as meningitis, necrotizing enterocolitis and bloodstream infections in neonates and infants. Information on the diversity, pathogenicity and virulence of Cronobacter species obtained from various sources is still relatively scarce and fragmentary. The aim of this study was to examine and analyse different pathogenicity and virulence factors among C. sakazakii and C. malonaticus strains isolated from clinical samples. METHODS: The thirty-six clinical Cronobacter strains have been used in this study. This bacterial collection consists of 25 strains of C. sakazakii and 11 strains of C. malonaticus, isolated from different clinical materials. Seven genes (ompA, inv, sip, aut, hly, fliC, cpa) were amplified by PCR. Moreover, the motility and the ability of these strains to adhere and invade human colorectal adenocarcinoma (HT-29) and mouse neuroblastoma (N1E-115) cell lines were investigated. RESULTS: Our results showed that all tested strains were able to adhere to both used cell lines, HT-29 and N1E-115 cells. The invasion assay showed that 66.7% (24/36) of isolates were able to invade N1-E115 cells while 83% (30/36) of isolates were able to invade HT-29 cells. On the average, 68% of the C. sakazakii strains exhibited seven virulence factors and only 18% in C. malonaticus. All strains amplified ompA and fliC genes. The other genes were detected as follow: sip 97% (35/36), hlyA 92% (33/36), aut 94% (34/36), cpa 67% (24/36), and inv 69% (25/36). CONCLUSIONS: C. sakazakii and C malonaticus strains demonstrate the diversity of the virulence factors present among these pathogens. It is necessary to permanently monitor the hospital environment to appropriately treat and resolve cases associated with disease. Furthermore, in-depth knowledge is needed about the source and transmission vehicles of pathogens in hospitals to adopt pertinent prevention measures.
Keywords: Bacterial Adhesion; buněčné linie; myši; Adherence; Foodborne Diseases; Clinical strains; Cronobacter malonaticus; faktory virulence; lidé; Cytological Techniques; cytologické techniky; Humans; epitelové buňky; Bacteriological Techniques; Mice; Animals; nemoci přenášené potravou; Epithelial Cells; Endocytosis; bakteriální adheze; zvířata; polymerázová řetězová reakce; Cronobacter; endocytóza; Virulence factors; enterobakteriální infekce; Polymerase Chain Reaction; Enterobacteriaceae Infections; Invasion; Cronobacter sakazakii; Virulence Factors; Cell Line; bakteriologické techniky